2019
DOI: 10.1186/s12916-018-1237-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation science and stigma reduction interventions in low- and middle-income countries: a systematic review

Abstract: Background Interventions to alleviate stigma are demonstrating effectiveness across a range of conditions, though few move beyond the pilot phase, especially in low- and middle-income countries (LMICs). Implementation science offers tools to study complex interventions, understand barriers to implementation, and generate evidence of affordability, scalability, and sustainability. Such evidence could be used to convince policy-makers and donors to invest in implementation. However, the utility of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 95 publications
2
88
0
Order By: Relevance
“…However, the review also found that they can play a very important part in providing social support to those affected, thereby helping in the mitigation of stigma. This ambivalent and dual nature of family, friends, and healthcare professionals has been noted by previous studies on HIV [ 73 , 74 , 75 , 76 ], depression [ 77 ], and leprosy [ 78 , 79 ] that have largely attributed it to the individual’s relevant knowledge, familiarity, and experience in regard to the disease—or lack thereof [ 73 , 74 , 75 , 77 ]. Similarly, we also identified the role of media as a “double-edged sword” as it often played a part as a source of stigma through negative portrayal and stereotyping of those affected [ 9 , 59 , 65 ], but sometimes also as a supportive agency in combating health-related stigma in society by raising awareness [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the review also found that they can play a very important part in providing social support to those affected, thereby helping in the mitigation of stigma. This ambivalent and dual nature of family, friends, and healthcare professionals has been noted by previous studies on HIV [ 73 , 74 , 75 , 76 ], depression [ 77 ], and leprosy [ 78 , 79 ] that have largely attributed it to the individual’s relevant knowledge, familiarity, and experience in regard to the disease—or lack thereof [ 73 , 74 , 75 , 77 ]. Similarly, we also identified the role of media as a “double-edged sword” as it often played a part as a source of stigma through negative portrayal and stereotyping of those affected [ 9 , 59 , 65 ], but sometimes also as a supportive agency in combating health-related stigma in society by raising awareness [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,15,59 Furthermore, they undermine the public health response and cause a negative impact on their overall effectiveness. 18,19,21 The findings of this study have several implications for public health research and practice in Indonesia. First, the prospects of stigma reduction response at different levels of the society are clear.…”
Section: Discussionmentioning
confidence: 85%
“…19,20 Low-and middle-income countries (LMICs) are known to be disproportionately affected by healthrelated stigma because of the existence of subjugating social norms, lack of health awareness, and inequitable access to health services that contribute to stigma and its negative effects. 21,22 However, much of the burden of health-related stigma in LMICs still remains hidden and unaddressed because of the lack of wider recognition in health policies and practices. 21 As the world's fourth-most populous developing nation currently in epidemiological transition with relatively high prevalence and distribution of noncommunicable and communicable diseases, Indonesia is particularly vulnerable to the burden of stigma compared with other Southeast Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual orientation and gender identity change efforts have been shown to cause significant harm, especially for LGBTI youth, and should not be sanctioned by any accrediting body or government [13,14]. Anti‐stigma interventions using participatory theatre, professional training and other modalities have been effective in reducing interpersonal stigma and healthcare stigma that underpin experiences of LGBTI violence [15‐17]. Ensuring that healthcare workers are trained to provide welcoming and competent care for LGBT people is key to engaging key populations effectively in HIV prevention and care and to promoting an effective human rights‐based response to the COVID‐19 pandemic.…”
mentioning
confidence: 99%